Determinants of unsuccessful tuberculosis treatment outcome in Southwest Ethiopia regional state public hospitals, 2022: a multi-center case control study - Berihe Hiluf, Solomon; Abera, Abebe; Bahiru, Mesfin; Kassie, Birhanu (Frontiers in Public Health, 2024)
Tuberculosis is the major cause of morbidity and is one of the top ten causes of death globally. In Africa the overall pooled estimate of unsuccessful tuberculosis treatment outcome was reported to be 21.1% which is above the world health organization defined threshold of 15%. Unsuccessful treatment outcome results drug resistance, prolonged period of infection and increased morbidity and mortality. Therefore the aim of study was to assess determinants of unsuccessful treatment outcome among tuberculosis patients in Southwest Ethiopia regional state public hospitals, 2022.Retrospective unmatched case-control study was employed by recruiting 570 study units (190 cases, 380 controls) in three randomly selected public hospitals from August 1-21,variable with a p-value of less than 0.05 in the multivariable logistic regression model was taken as statistically significant. The odds ratio and 95% confidence level was used to measure the strength of the association.RESULT: A total of 561 records (187 cases and 374 controls) were included from tuberculosis registers. In this study, the factors independently associated with unsuccessful tuberculosis treatment outcome were older age (AOR=1.